Defining and identifying stakeholders: Views from management and stakeholders - S. Benn; R. Abratt; B. O'Leary (South African Journal of Business Management, 2016)
The focus of an organisation's marketing efforts has shifted in recent years from satisfying customer needs to value creation for stakeholders. The purpose of this research is to establish how the senior management of an organisation define and identify stakeholders. The organisation's stakeholders are then asked to identify their role as stakeholders. The research employed a qualitative research design. The subjects being the senior management of the South African subsidiary of one of the world's largest paint manufacturers as well as a sample of the firm's stakeholders. The results reveal a set of primary and secondary stakeholders that include some differences from current stakeholder theory. The results also confirm the importance of legitimacy as well as the new finding of the importance of reciprocity in stakeholder attributes. From a marketing point of view the focus of the organisation should not be on customers alone but include all stakeholders. This will mean that organisations should focus on stakeholder satisfaction and developing strategies that recognize the importance of all legitimate stakeholders.
Keywords: 650